Augmented Astronomy for Science Teaching and Learning - Huerta-Cancino, L (Springer Science and Business Media Deutschland GmbH, 2024)
Often, students’ ‘prior ideas’ and ‘alternative conceptions’ about natural phenomena do not align with established scientific models in science education. In the field of astronomy, some of these ideas and conceptions are ingrained from an early age and persist over the years even after receiving formal instruction, highlighting the urgent need to design resources and activities to enhance scientific literacy. In this regard, Extended Reality (XR) emerges as an easily accessible technology with broad applications for astronomy education, making it a useful tool with the potential to address this issue. From this perspective, this study aims to present the design and preliminary evaluation of eight Augmented Reality (AR) educational resources focused on addressing reported alternative conceptions during the learning and teaching of astronomy. Through a methodology based on Educational Design Research, we developed and preliminarily evaluated these astronomy AR resources through simple activities with primary and secondary school students. The evaluation results contributed to improving the software, providing students with access to rigorous scientific content focused on overcoming alternative conceptions in astronomy and tailored to their needs. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.